1988
DOI: 10.1159/000226568
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemosensitivity: Augmentation by Hyperthermia of Cytotoxicity of Anticancer Drugs against Human Colorectal Cancers, Measured by the Human Tumor Clonogenic Assay

Abstract: Thermochemosensitivity was examined in vitro by a human tumor clonogenic assay (HTCA) using specimens obtained surgically from 43 patients with colorectal cancer. We found that the percentages of patients whose cells showed higher sensitivity (greater than 70% inhibition of colony formation) to hyperthermia alone were 29.6 and 55.6% at 42 and 43 °C each for 1 h, respectively. Similarly, percentages of patients whose cells were sensitive to drugs alone were 13.8, 24.1 and 48.3%, for cis-diamminedichloroplatinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The thermosensitivity of melanoma and colorectal cancer has been examined in vitro using the same HTCA technique under the same experimental conditions as this study, 428C for 1 h. Mann et al 11 reported that in melanoma, 25% of 53 cases were heat-sensitive by the criterion of T/C% µ 25%, and Murakami et al 12 reported that in colorectal cancer, 30% of 27 cases were sensitive (T/C% µ 30%). In the present study, 19.6% of 46 Rb tumours had a T/C% µ 30%, and 13.0% had a T/C% µ 25% (®gure 1).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The thermosensitivity of melanoma and colorectal cancer has been examined in vitro using the same HTCA technique under the same experimental conditions as this study, 428C for 1 h. Mann et al 11 reported that in melanoma, 25% of 53 cases were heat-sensitive by the criterion of T/C% µ 25%, and Murakami et al 12 reported that in colorectal cancer, 30% of 27 cases were sensitive (T/C% µ 30%). In the present study, 19.6% of 46 Rb tumours had a T/C% µ 30%, and 13.0% had a T/C% µ 25% (®gure 1).…”
Section: Discussionmentioning
confidence: 95%
“…To address this issue, Rb cells were obtained directly from fresh surgical specimens and their sensitivity to heat and various antitumour agents given at physiological or elevated temperatures was investigated in vitro. Similar studies performed on human tumours such as melanoma 11 and colorectal cancer 12 have successfully used the HTCA (human tumour clonogenic assay) established by Hamburger and Salmon 13 . This assay has been adapted to study the sensitivity of Rb cells to antitumour agents and preliminary results have been reporte d previously 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A combination of cytoreductive surgery (CRS) with perioperative intraperitoneal chemotherapy (PIC) was proposed by Sugarbaker (8). The rationale behind this strategy was to resect visible disease and any occult residual disease would be treated with a high concentration of chemotherapy and hyperthermia which mutually potentiate one another's effects (9,10). Fifteen years and 600 publications later (7), a systematic review of this novel treatment concluded that this combined approach was very probably superior to conventional therapy, even in the absence of controlled M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 5 randomized trials, and even with evidence from only five series of more than 100 cases (11)(12)(13)(14)(15)(16).…”
Section: Accepted Manuscript 4mentioning
confidence: 99%